Peningkatan Kemampuan Berliterasi Melalui Hadirnya Pondok Baca Maju Lestari Desa Cibeber Kecamatan Kiarapedes Kabupaten Purwakarta - Nasution, Ananda Bunga (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
The reading interest of the people of Cibeber village is still relatively low, this fact is indeed very concerning. Children spend more time playing gadgets at home and rarely socialize other than during school. One of the problems of low literacy in children, because they do not have book and library facilities to learn, the solution is done to foster children's interest in reading with the Program, namely providing community Reading Huts. This research study applies a qualitative approach with a descriptive method where this research is intended to explain the circumstances or events that occur when this activity is running. This study aims to obtain an empirical and holistic picture of the role of the community Pondok Baca in fostering interest in reading in the people of Cibeber village. The Cibeber village group took the Pondok Baca procurement program by describing the implementation of activities in several stages, namely Planning, Licensing, Implementation, Decoration, Evaluation, Introduction, Inauguration.